Multidisciplinarity in a psychosocial care center for users of alcohol and other drugs - Veloso, Lorena Uchôa Portela; Brito, Ana Angélica Oliveira de; Rodrigues, Lana de Pinho; Veloso, Caique; Junior, Fernando José Guedes da Silva; Monteiro, Claudete Ferreira de Souza (Rev Rene, 2016)
Objective: to analyze the conception of health professionals about multidisciplinary work.Methods: qualitative study carried out with twelve health professionals from a Psychosocial Care Center for Alcohol and Drugs. Data were produced through interviews and submitted to content analysis. Results: three categories were elaborated addressing the professionals’ conceptions about the multidisciplinary work, the practical strategies used in the daily life of the service for its implementation and the main challenges for the consolidation of the multidisciplinarity as a tool to assist the users of the service. Conclusion: professionals understand the relevance of multidisciplinary work, but stated that it requires planning and valuing the knowledge of the other. Obstacles in academic training and deficiencies in the physical structure of services were identified as the main challenges for multidisciplinarity to go beyond the intentions to become a concrete practice.